Shifting Boundaries: Ecological and Geographical Range extension Based on Three New Species in the Cyanobacterial Genera Cyanocohniella, Oculatella, and, Aliterella. Issue 5 (27th June 2020) - Jung, Patrick; Mikhailyuk, Tatiana; Emrich, Dina; Baumann, Karen; Dultz, Stefan; Büdel, Burkhard
Abstract : The polyphasic approach has been widely applied in cyanobacterial taxonomy, which frequently led to additions to the species inventory. Increasing our knowledge about species and the habitats they were isolated from enables new insights into the ecology of newly established genera and species allowing speculations about the ecological niche of taxa. Here, we are describing three new species belonging to three genera that broadens the ecological amplitude and the geographical range of each of the three genera. Cyanocohniella crotaloides sp. nov. is described from sandy beach mats of the temperate island Schiermonnikoog, Netherlands, Oculatella crustae‐formantes sp. nov. was isolated from biological soil crusts of the Arctic Spitsbergen, Norway, and Aliterella chasmolithica originated from granitic stones of the arid Atacama Desert, Chile. All three species could be separated from related species using molecular sequencing of the 16S rRNA gene and 16S–23S ITS gene region, the resulting secondary structures as well as p‐distance analyses of the 16S–23S ITS and various microscopic techniques. The novel taxa described in this study contribute to a better understanding of the diversity of the genera Cyanocohniella, Oculatella, and Aliterella in different habitats.